Comparison Between Hysteresis and Predictive Control with Optimized Vector Selection for Direct Power Control to a Shunt Active Power Filter - Ruben da C. Ferreira; Pedro H. de M. Martins; Nady Rocha; Edison R. C. da Silva; Victor F. M. Bezerra Melo (Eletrônica de Potência)
In this paper, the performance of a shunt active power filter using direct power control based on the hysteresis method and model predictive control is discussed. Furthermore, an optimized vector selection is presented for model predictive control. This paper’s objective is to evaluate the processing time, reduction of harmonic components that would be injected into the electrical grid by a non-linear load, power semiconductor losses, average switching frequency and root mean square error for the control variables. The comparison uses the same system model and parameters for both strategies. Simulation and experimental results are presented. Using the strategy discussed in this paper, it was possible to reduce harmonic components in the electrical grid, with reduced time for vector selection.